PATHOLOGICAL, ANATOMICAL, AND HISTOPATHOLOGICAL STUDY OF SUSPECTED CANINE DISTEMPER IN A POMERANIAN-MIXED LOCAL DOG - Yudha Yaksa Crada Yoga Arum Raharjo; I Ketut Berata (Buletin Veteriner Udayana, 2025)
A 2-month-old male dog with suspected canine distemper virus (CDV) infection was necropsied on 27 February 2025. The dog exhibited clinical signs including anorexia, weakness, diarrhea, dyspnea, and ocular/nasal exudate. Gross and histopathological examinations were performed. Tissue samples from the brain, heart, trachea, lungs, liver, spleen, kidneys, intestines, and urinary bladder were collected during necropsy and fixed in 10% neutral buffered formalin (NBF). Histopathological sections were prepared and stained with hematoxylin and eosin (H&E). Gross pathological findings included cerebral sulcal congestion, tracheal pallor, pulmonary necrosis, blunted cardiac apex, mild hepatic hemorrhage, splenomegaly, indistinct corticomedullary junction in the kidneys, urinary bladder hemorrhage, and intestinal hemorrhage. Microscopically, lesions included encephalitis, ulcerative necrotizing tracheitis, interstitial pneumonia, hemorrhagic myocarditis, hemorrhagic hepatitis, necrotizing glomerulonephritis, necrotizing cystitis, hemorrhagic and necrotizing enteritis, and splenic lymphoid depletion. Based on the case history, clinical signs, gross pathology, and histopathological findings, the dog was definitively diagnosed with canine distemper.